Haemoglobin Epsilon as a Biomarker for the Molecular Detection of Canine ‎Lymphoma - H Al-Kinani, Layla; A Sharp, Margaret; M Wyatt, Kenneth; Coiacetto, Flaminia; R Sharp, Claire; Rossi, Gabriele; K Greene, Wayne (The Iraqi Journal of Veterinary Medicine, 2023)
Lymphoma is a cancer arising from B or T lymphocytes that are central immune system ‎components. It is one of the three most common cancers encountered in the canine; ‎lymphoma affects middle-aged to older dogs and usually stems from lymphatic tissues, ‎such as lymph nodes, lymphoid tissue, or spleen. Despite the advance in the management of ‎canine lymphoma, a better understanding of the subtype and tumor aggressiveness is still ‎crucial for improved clinical diagnosis to differentiate malignancy from hyperplastic ‎conditions and to improve decision-making around treating and what treatment type to use. ‎This study aimed to evaluate a potential novel biomarker related to iron metabolism, ‎embryonic haemoglobin (HBE), for early diagnosis. Archived samples in combination with ‎prospective samples collected from dogs with and without lymphoma were used in this ‎study for the retrospective analyses of this tumor based on the same biomarker amplified by ‎real-time quantitative polymerase chain reaction. The HBE mRNA was aberrantly expressed ‎in canine B and T cell lymphoma compared to the normal lymph node tissue and ‎hyperplastic lymph nodes. In conclusion, this study identified a novel potential biomarker for improving lymphoma ‎diagnosis and treatment in dogs. Further studies with larger sample sizes are needed to ‎confirm the suitability of this biomarker for canine lymphoma diagnosis.